Conformity-nonconformity and heuristic-algorithmic behaviour (KANH-III) among serial, portfolio, and novice entrepreneurs. - Jarosław Ropęga (22291903) (2025)
Conformity-nonconformity and heuristic-algorithmic behaviour (KANH-III) among serial, portfolio, and novice entrepreneurs.